2009
DOI: 10.1039/b821947h
|View full text |Cite
|
Sign up to set email alerts
|

Multimetallic arrays: Symmetrical bi-, tri- and tetrametallic complexes based on the group 10 metals and the functionalisation of gold nanoparticles with nickel-phosphine surface units

Abstract: Homobimetallic complexes of nickel, palladium and platinum, [(L2M)2(S2CNC4H8NCS2)]2+, are formed on reaction of the piperazine bis(dithiocarbamate) linker, KS2CNC4H8NCS2K, with [MCl2L2] (M=Ni, L2=dppe, dppf; M=Pd, L2=dppf; M=Pt, L=PEt3, PMePh2, PPh3, L2=dppf). [{Pd(C,N-C6H4CH2NMe2)}2(S2CNC4H8NCS2)] can be obtained in the same way. On reaction of [MCl2L2] (M=Pd, Pt) with the zwitterion S2CNC4H8NH2, a symmetrisation process occurs to yield a mixture of the complexes [M(S2CNC4H8NH2)L2]2+ and [(L2M)2(S2CNC4H8NCS2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Since 2008, we have focused on the functionalisation of gold nanoparticles (GNPs) with transition metal units . Much of this work has focused on the use of dithiocarbamate (R 2 NCS 2 − ) tethers rather than the usual thiol(ate) or disulfide attachment methodologies.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…Since 2008, we have focused on the functionalisation of gold nanoparticles (GNPs) with transition metal units . Much of this work has focused on the use of dithiocarbamate (R 2 NCS 2 − ) tethers rather than the usual thiol(ate) or disulfide attachment methodologies.…”
Section: Introductionsupporting
confidence: 67%
“…Addition of K 2 CO 3 followed by carbon disulfide leads to the formation of the expected dithiocarbamate moiety (compound 7), in line with our previous studies on piperazine-based dithiocarbamatec omplexes. [16,17,26] As discoveredi nt hese earlier studies, the long-term stability of 7,both in solution and in the solid state, was found to be significantly worse than that of 6, so compound 7 was always generated in situ when desired, but not isolated. High-resolution mass spectrometry experimentsn evertheless confirmed the generationo f7 (m/z 702.1025).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…An exciting new development in the area of golddithiocarbamate chemistry is the stabilization of gold nanoparticles by chelating dithiocarbamate ligands [92][93][94][95][96][97]. These are extremely easy to prepare, show good stability and allow decoration of the nanoparticles with a range of different functional groups.…”
Section: Tris(dithiocarbamate)mentioning
confidence: 99%